(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article delves into the significance of integrating functional literacy into primary education, emphasizing its practical applications beyond basic reading and writing skills. It highlights the importance of equipping students with the ability to comprehend, analyze, and apply information in real-world contexts from an early age. The article explores strategies for implementing functional literacy in primary education, including curriculum design, teacher training, active learning methods, technology integration, and community engagement. By promoting a holistic approach to literacy instruction, schools can empower students to become lifelong learners who are prepared to navigate the challenges of an ever-changing society.